Midline mini-incision approach with superolateral facet joint quadrantectomy for extraforaminal disc herniations: A modified technique and outcomes - Kuytu, Turgut; Karaoğlu, Ahmet; Bayat, Muhammet; Bayram, Serdar (The European Research Journal, 2025)
Objectives: Extraforaminal disc herniations constitute 3-12% of all lumbar disc herniations. In the literature, many surgical procedures have been described for extraforaminal disc herniations, including roughly medial and lateral approaches. In our study, we discussed the clinical results of cases in which we applied the superolateral quadrantectomy (resection of the superolateral quarter of the facet joint) technique described in the literature but modified by us, and we made conclusions about the technique. Patient outcomes were evaluated using the Macnab criteria: excellent, good, fair, and poor. Methods: Between 2019 and 2023, 72 patients who were operated on with the diagnosis of single-level extraforaminal lumbar disc herniation and underwent superolateral facet joint quadrantectomy via mini incision-midline approach in our clinic were retrospectively analyzed. Results: Preoperative Visual Analog Scale scores were 4-10 (mean: 8.5±2.17). Postoperative scores were 0-1 (mean: 0.3±0.1). According to the Macnab classification, 37 (51.39%) of the patients were evaluated as excellent, and 27 (37.50%) in the third postoperative month. Postoperative follow-up dynamic radiographs showed no instability in patients at the end of the 1st year. There were no perioperative complications in any of the cases. Conclusions: The modified technique that we have described offers the potential advantages of preserving the facet joint capsule and reducing the size of the incision.